The Mixture: Truth, Beauty, Proportion. Damascius, In Philebum (Circe de clásicos y modernos, 2024)
Some notes taken down by students during Damascius’s lectures on Plato’s Philebus provide a Neoplatonic interpretation of the elusive concept of the Good. Damascius emphasizes the parallel between dialectic and differentiation, stemming from the segmentic distribution of the One. This division method leads to a triad that co-aggregates the duality of Limit and Infinite in the Mixture. Truth, beauty, and proportion coordinate the plurality and are directed toward the goal of the supreme Good. Desirability, adequacy, and perfection are the essential conditions that guide the soul toward this goal, which is revealed analogously in Being, Life, and Intellect.
Keywords: Damascius; Neoplatonism; Mixture; Being; Life; Intellect